Device-To-Device (D2D) Communication in Cellular Network - Performance Analysis of Optimum and Practical Communication Mode Selection - Hakola, Sami; Tao Chen; Lehtomäki, Janne; Koskela, Timo (2010 IEEE Wireless Communication and Networking Conference, 2010)
In a cellular network system one way to increase its capacity is to allow direct communication between closely located user devices when they are communicating with each other instead of conveying data from one device to the other via the radio and core network. The problem is then when the network shall assign direct communication mode and when not. In previous works the decision has been done individually per communicating device pair not taking into account other devices and the current state of the network. We derive means for getting optimal communication mode for all devices in the system in terms of system equations. The system equations capture information of the network such as link gains, noise levels, signal-to-interference-and-noise-ratios, etc., as well as communication mode selection for the devices. Using the derived equations performance bounds for the cellular system where D2D communication is an additional communication mode are illustrated via simulations. Further, practical communication mode selection algorithms are used to evaluate their system performance against the achievable bounds. Analysis show the usability of the system equations and the potential of having D2D operation integrated into a cellular system when there is enough local communication occurring.